Penerapan Aktivitas Fisik Jalan Kaki Terhadap Perubahan Kadar Gula Darah Sewaktu Pada Penderita Diabetes Mellitus - Mutiara Mutiara; Bangun Dwi Hardika; Lilik Pranata (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Diabetes mellitus is classified into a group of metabolic diseases with special characteristics of increased blood sugar levels or hyperglycemia, which is caused by abnormalities in insulin secretion or abnormalities in insulin work. Physical activity can also affect blood sugar levels, one of which is the type of physical exercise recommended for people with diabetes mellitus, walking. This research design is experimental in the form of a one group pretest-posttest design. This research was carried out by providing physical activity intervention by walking 3 times a week for 20 minutes. Based on the application of EBP, the results obtained from 3 research respondents experienced a decrease in blood glucose levels every day with different differences. This can be proven that non-pharmacological therapy using walking physical activity is effective and can be used to reduce blood glucose levels in diabetes mellitus sufferers. . It is hoped that the results of this research can provide insight to diabetes mellitus sufferers in efforts to manage diabetes mellitus with the physical activity of walking and can have implications for this.